The Influence of the Ability to Read Food Labels on Compliance with Reading Food Product Labels among Nutrition Students of Provinsi Kepulauan Riau - Anggraini, Citra Dewi; Rosyidah, Haqqelni Nur; Rizma, Amalina; Herviana; Pratiwi, Siska; Desy (Future Science, 2024)
Reading food labels among students is currently important to prevent consume excessive amounts of certain nutrients, resulting in excess nutrition or deficiencies in certain nutrients needed by the body. Substance information obtained from food labels is an important source of nutritional information but is usually underutilized by consumers. The information on food labels helps consumers become savvy about their food choices. This research using cross sectional design. Respondents in this study were students from the students of the nutrition undergraduate study program in Institut Kesehatan Mitra Bunda with a total of 47 respondents. Sample selection was carried out using purposive sampling. The data collection method in this study was through a questionnaire. Respondent’s will fill in the questionnaire given themselves by following the instructions that will be explained before filling out the questionnaire by the data collection team. Data on respondents' ability to read nutritional value information labels was obtained from several multiple choice questions regarding the quantitative information contained in the food labels. It was found that of the 38 respondents who had good ability to read nutritional value information labels, there were 55.3% (21 respondents) who did not comply with reading nutritional value information labels. Then the statistical test results obtained were 0.908. Majority of respondents have good abilities but are not obedient in reading nutritional value information labels. The behavior of reading food labels can be used as a preventive and promotive to maintain health.